Cultural landscape : sustaining the heritage value and protecting local identity - Md Jani, Haza Hanurhaza; Mohd. Hussain, Mohd. Ramzi (IIUM Press, 2011)
This paper presents a review on the concept of cultural landscape in sustaining the heritage value and protecting local identity. It presents the notion of revealing and sustaining the great diversity of the interaction between humans and their environment, to protect living traditional cultures and preserve the traces of those which have disappeared. It is actually an approach to appreciate pure relationship between human and built environment. Landscapes contain valuable heritage and historic values developed from layers of historical incident and occurrence by human including traditional cultural values. This incident eventually became human legacy as the heritage values and traditions are passed from one generation to another. Islam highlights the important of human relationship with the environment and the associations involving the two assemblages have been emphasized repeatedly in AI-Quran. "And if thy LORD Had so Willed, He Could Have Made the people one nation, and they would still differ" (11: 118). The aim of this paper is to highlight the important heritage values of cultural landscape towards enriching people's identity, develop a sense of place or belonging and protecting the original culture. The paper incorporated three fundamental frameworks that sustaining the heritage and value and protecting local identity_which are i) sense of attachment, ii) sense of pride and iii) identity of the place that covers the explanation of human root, identity, image, character and values. It is hoped that the paper will contributes to further enrich the important knowledge of cultural landscape in sustaining the heritage values and protecting the local identity.